Norharmane rhenium(I) polypyridyl complexes: synthesis, structural and spectroscopic characterization - Maisuls, Iván (2015)
Two novel Re(I) complexes with the general formula fac-[Re(CO)3(L)(nHo)]CF33SO3, where L = 2,2’-bipyridine (bpy) or 1,10 phenanthroline (phen) and nHo (9H-pyrido[3,4-b]indole; norharmane) have been synthesized. The Re(I)–nHo complexes were characterized by structural X-ray diffraction, 1H and 13C NMR, UV-vis absorption and FT-IR spectroscopy, and by a combination of two mass spectrometry techniques, namely ESI-MS and UV-MALDI-MS. All characterizations showed that nHo is coordinated to the metal atom by the pyridine nitrogen of the molecule. X-ray structural analysis revealed that the crystal lattices for both complexes are further stabilized by a strong >N–H⋯O bond between the pyrrole NH group of the pyridoindole ligand and one oxygen atom of the trifluoromethanesulfonate counter-ion. Ground state geometry optimization by DFT calculations showed that in fluid solution the nHo ligand may rotate freely. The nature of the electronic transitions of Re(CO)3(bpy)(nHo)⁺ were established by TD-DFT calculations. The set of the most important electronic transitions present in this complex are comprised of π → π* electronic transitions centered on bpy and nHo moieties, LLCTnHo→COs, MLLCTRe(CO)3→bpy and LLCTnHo→bpy transitions. Additionally, TD-DFT calculations predict the existence of another two intense MLLCTRe(CO)3→nHo electronic transitions. Calculated UV-vis absorption spectra are in good agreement with the corresponding experimental data for the bpy-containing complex.